Role of astrocytes and microglia in hepatic encephalopathy associated with advanced chronic liver disease: lessons from animal studies - Wouter Claeys; Anja Geerts; Lien Van Hoecke; Christophe Van Steenkiste; Roosmarijn E. Vandenbroucke (Neural Regeneration Research)
Hepatic encephalopathy, defined as neuropsychiatric dysfunction secondary to liver disease, is a frequent decompensating event in cirrhosis. Its clinical impact is highlighted by a notable increase in patient mortality rates and a concomitant reduction in overall quality of life. Systemically, liver disease, liver function failure, portosystemic shunting, and associated multi-organ dysfunction result in the increase of disease-causing neurotoxins in the circulation, which impairs cerebral homeostasis. Key circulating neurotoxins are ammonia and inflammatory mediators. In the brain, pathophysiology is less well understood, but is thought to be driven by glial cell dysfunction. Astrocytes are the only brain resident cells that have ammonia-metabolizing machinery and are therefore putatively most susceptible to ammonia elevation. Based on a large body of mostly in vitro evidence, ammonia-induced cellular and molecular disturbances include astrocyte swelling and oxidative stress. Microglia, the brain resident macrophages, have been linked to the translation of systemic inflammation to the brain microenvironment. Recent evidence from animal studies has provided novel insights into old and new downstream effects of astrocyte and microglial dysfunction such as toxin clearance disruption and myeloid cell attraction to the central nervous system parenchyma. Furthermore, state of the art research increasingly implicates neuronal dysfunction and possibly even irreversible neuronal cell death. Cell-type specific investigation in animal models highlights the need for critical revision of the contribution of astrocytes and microglia to well-established and novel cellular and molecular alterations in hepatic encephalopathy. In this review, we therefore give a current and comprehensive overview of causes, features, and consequences of astrocyte and microglial dysfunction in hepatic encephalopathy, including areas of interest for future investigation.